Rapport om verksamheten i den regionala SI-plattformen 17/18 : En samverkan mellan högre utbildning, gymnasie- och grundskolor - Fredriksson, Johan; Bryngfors, Leif; Mörner, Lise-Lotte (Lund University, 2018)
Supplemental Instruction (SI) is an academic support model with large international prevalence with the purpose of preventing dropouts and strengthen students’ study abilities and results. SI is a collaborative form of learning in groups of about 5-15 students who meet on a weekly basis under the facilitation of an SI-leader, an older student with good insight in the course. The SI-leader helps the students to succeed in high-risk courses in heterogeneous groups. A relaxed atmosphere, inner motivation and a collaborative academic-social learning characterize the SI-sessions. This report provides a description of the Regional SI-platform and its development since the start in 2016 and contains an evaluation of the academic year of 17/18. At the publishing date of this report (September 2018) we can state the following about the regional SI-platform: - it is active in over 20 municipalities in the provinces of Skåne, Halland och Blekinge, - it comprises five Higher Education Institutes (HEIs) in Lärosäten Syd (a collaboration between six HEIs in southern Sweden), - it includes around 30 upper secondary schools and 10 lower secondary schools, - during the academic year of 17/18 over 1000 SI-participating students were involved where of approximately 70 % were active on a weekly basis, - during the academic year of 17/18 around 140 SI-leaders from both tertiary and secondary schools were trained and engaged in secondary schools - the number of contact hours during the academic year of 17/18 is up to 7500 (contact hours are the total number of hours students visit sessions during a year), - around 50 teachers have been trained in the SI programmes, - the average attendance on SI sessions is ~8, - SI has spread to a broad range of subjects such as maths, Swedish, economy, Swedish as a second language, modern languages, chemistry, physics and music, - SI is active in the following upper secondary programs: The Child Recreation- , The Arts-, The Business and Administration-, The Industrial-, The Natural Science-, The Health Care-, and The Social Science Programme, - it is a pioneering model with big interest both nationally and in the international SI-community. The SI-participants, the SI-leaders, the schools’ contact persons and principals who have participated in the Regional SI-platform during the academic year of 17/18 are generally very satisfied with the SI-operations. Students, SI-leaders and contact persons are mainly expressing that SI has a positive effect on the SI-participants’ studies, contributed to a deeper understanding of their coursework, contributed to a development of team-working and collaborating skills, contributed to the ability to present material and problems to others, and have prepared and inspired students to higher education. The SI-sessions seems to have had a stress-free and pleasant atmosphere. The SI-leaders experience a personal development and increased self-confidence, comfort with leading a group and they are satisfied with the support from the SI-center. The evaluation is not an absolute proof for the effects of SI but the accumulated view from the vast gather amount of data from surveys and group-discussions with SI-participants, SI-leaders, contact persons and principals indicates that SI has made a positive contribution in these areas. The coordinating SI-center at Lund University experiences a deepened relationship with the other participating universities, upper and lower secondary schools and are delighted that SI is viewed so positively. The focus into the future is to develop the quality and long-term vitality at the participating schools rather than a quick expansion. The three central components in this focus is to: - secure a long-term funding, - harmonize the work of the universities’ SI-coordinators, - and to ensure sustainable conditions for the hosting schools’ contact persons to coordinate the SI-operations.